Parker ink-KOH stain, Chicago Sky Blue (CSB) stain, and Fungi Culture, for The Diagnosis of Superficial Dermatomycoses - Sunarso Suyoso; Anggraeni Noviandini; Linda Astari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Superficial dermatomycoses are infections of skin, nails, and hair that can be divided into dermatophyte, pityriasis versicolor (PV), and candidiasis based on the causative pathogens. Rapid diagnosis is important to initiate the treatment earlier. To establish the diagnosis, direct microscopy using potassium hydroxide and culture examinations could be performed. Although the routine examination using Parker ink-KOH staining could be done in very short time, it was lacking of color contrast and requiring considerable skill interpretation. Various contrast dyes are available including a new contrast Chicago Sky Blue (CSB) staining. Purpose: To evaluate the result of Parker ink-KOH stain, CSB stain, and culture for the diagnosis of superficial dermatomycoses. Methods: The study was an observational descriptive research. Skin scrappings from patients with clinical diagnosis of superficial dematomycoses in Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital were examined using Parker ink-KOH stain, CSB stain, then interpreted by a researcher and analysts. The samples were also cultured. Results: A total of 45 samples, 71.1% revealed dermatophyte patients, 22.2% PV patients, and 6.7% candidiasis patients. The fungal filaments were detected in Parker ink-KOH stain by researcher 91.11% of the samples and by analysts 95.56%. CSB stain were detected 100% in all the samples by both observers. The culture was positive in 71.1% samples. Conclusion: CSB stain provides a good color contrast and shown a promising examination as it is rapid, simple, and easy to interpret for the diagnosis of superficial dermatomycoses, thus it is suitable to apply for inexperienced clinicians in dermtology clinical setting and laboratory.